Evaluation methods and engineering applications of in-situ stress in deep, strong heterogeneity terrestrial shale oil and gas reservoirs: a case study of jurassic shales in the Yingshan-Pingchang area, northeast Sichuan - Yin, Shujun; Zhang, Jianliang; Deng, Hucheng; Qin, Hao; Xia, Wenhao; Du, Yu; Gong, Ming; Huang, Tao; Li, Chang (Frontiers in Earth Science, 2025)
IntroductionThe Jurassic terrestrial shale in the Yingshan–Pingchang area of the northeastern Sichuan Basin holds substantial exploration and development potential. However, the area exhibits significant vertical heterogeneity and anisotropy in in-situ stress. Thus, precise vertical evaluation of in-situ stress is urgently required to provide a scientific basis for selecting hydraulic fracturing layers in future operations.MethodsThis study conducted a detailed in-situstress analysis utilizing paleomagnetic data, velocity anisotropy measurements, differential strain experiments, hydraulic fracturing results, and both conventional and specialized logging data. A transversely isotropic in-situstress prediction model was developed to evaluate the stress distribution, aiming to identify target layers favorable for hydraulic fracturing.ResultComprehensive analysis indicates that the in-situstress orientation of Jurassic shale in the Yingshan-Pingchang area generally aligns with the regional stress orientation (NE90° ± 10°). Due to the influence of local NW-trending structures, the in-situstress orientation exhibits a clockwise deflection. In the Jurassic formation, the maximum horizontal principal stress ranges from 42.33 MPa to 102.56 MPa, averaging 74.89 MPa; the minimum horizontal principal stress ranges from 39.20 MPa to 84.04 MPa, averaging 67.20 MPa; and the vertical principal stress varies between 31.91 MPa and 91.39 MPa, averaging 60.23 MPa. These findings were corroborated by in-situstress measurements obtained through hydraulic fracturing, demonstrating that the stress magnitudes determined via differential strain analysis are highly accurate. The analysis of the three-dimensional stress relationships indicates that the study area predominantly exhibits a strike-slip faulting regime. Comparative analysis reveals that the minimum principal stress gradient in shale is higher than that in limestone and sandstone. Furthermore, the transverse isotropic in-situstress prediction model demonstrates high accuracy. When comparing its predictions for minimum and maximum horizontal principal stresses to measured in-situstress data, the model exhibits average relative errors of only 3.39% and 3.23%, respectively.DiscussionIn the study area, vertical high-low-high (HLH) stress difference profiles exhibit the highest oil-bearing potential and a reduced likelihood of fracturing-induced artificial fractures crossing through layers. This makes HLH profiles the optimal structural type for selecting fracturing stages in in-situstress difference fracturing operations.